2014
DOI: 10.5811/westjem.2014.4.21365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Web-based Educational Module on Pediatric Emergency Medicine Physicians’ Knowledge, Attitudes, and Behaviors Regarding Youth Violence

Abstract: Introduction:Youth seen in the emergency department (ED) with injuries from youth violence (YV) have increased risk for future violent injury and death. Pediatric emergency medicine (PEM) physicians rarely receive training in, or perform, YV screening and intervention. Our objective was to examine effects of a web-based educational module on PEM physicians' knowledge, attitudes, and behaviors regarding YV screening and interventions in the ED.Methods:We invited all PEM fellows and attendings at an urban Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Development of education to address psychiatric prescribers' knowledge deficits, uninformed attitudes, and poor prescribing practices that prevent LAIs from being utilized as a treatment option in those with schizophrenia is needed. Studies have indicated that the use of toolkits can facilitate translation of evidence into practice (Yamada et al, 2015), and web-based education has shown promise at improving the knowledge, attitudes, and practices of medical professionals (Madsen et al, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Development of education to address psychiatric prescribers' knowledge deficits, uninformed attitudes, and poor prescribing practices that prevent LAIs from being utilized as a treatment option in those with schizophrenia is needed. Studies have indicated that the use of toolkits can facilitate translation of evidence into practice (Yamada et al, 2015), and web-based education has shown promise at improving the knowledge, attitudes, and practices of medical professionals (Madsen et al, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…It has been used to understand and contextualize the relative uptake of computed tomography clinical imaging rules 34 and has also been used to design clinical curriculums that successfully modified the behavioral intentions of EPs. 35 More recently, Samuels et al and Choo et al used TPB as a framework to inform changes in opioid-related clinical behaviors among clinicians in the ED. 36 , 37 …”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…While this study had a small sample size and lacked a control group, the literature demonstrates that similar sample sizes and design have been used for initial intervention evaluation. 33,34,35 Data was collected from a single, Midwestern urban pediatric ED, thus findings may not be generalizable to trainees in varied geographic locations. Due to the rotating nature of trainees in the ED, we only obtained immediate post-intervention assessments and do not know if changes will be sustained over time.…”
Section: Limitationsmentioning
confidence: 99%